Tetra-mu-acetato-bis{[1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene]rhodium(II)}(Rh-Rh) tetrahydrofuran tetrasolvate - Andre, Vania (2015)
In this paper, we compare and discuss the very different crystal structures and supramolecular arrangements obtained when using different crystallization solvents with the same organometallic moiety. The new title tetrahydrofuran (THF) solvate, [Rh-2(C2H3O2)(4)(C27H36N2)(2)]center dot 4C(4)H(8)O, is compared with the toluene trisolvate reported previously by us [Gois, Trindade, Veiros, Andre, Duarte, Afonso, Caddick & Cloke (2007). Angew. Chem. Int. Ed. 46, 5750-.5753]. The molecular structures of the two complex molecules display a similar conformation, but due to the presence of different solvent molecules, the two solvates crystallize in different space groups and exhibit quite diverse supramolecular assemblies. The toluene solvate crystallizes in the triclinic space group P (1) over bar, while in the presence of THF, the monoclinic P2(1)/c space group is obtained, with the complex molecule residing on an inversion centre. The resulting crystal packing displays no classical hydrogen bonds but different supramolecular synthons give rise to different packing motifs. In this work, we highlight the different supramolecular architectures obtained when organometallic moieties crystallize with different solvent molecules. We compare the novel structure of the THF derivative with that of the toluene solvate of a dirhodium(II) complex belonging to a new family of catalyst compounds exhibiting very high performance in arylation processes.. - Fundacao para a Ciencia e Tecnologia [POCI2010]; FEDER [PTDC/QUI/66695/2006, PTDC/QUI/66015/2006, POCI/QUI/60175/2004, POCI/QUI/58791/2004, SFRH/BPD/18624/2004, SFRH/BD/30619/2006, SFRH/BD/40474/2007]. - The authors acknowledge funding of the project by Fundacao para a Ciencia e Tecnologia (grant No. POCI2010) and FEDER (grant Nos. PTDC/QUI/66695/2006, PTDC/QUI/66015/2006, POCI/QUI/60175/2004, POCI/QUI/58791/2004, SFRH/BPD/18624/2004, SFRH/BD/30619/2006 and SFRH/BD/40474/2007)